2020
DOI: 10.3390/biom10060907
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Specific Glucoimidazole and Mannoimidazole Binding by Os3BGlu7

Abstract: β-Glucosidases and β-mannosidases hydrolyze substrates that differ only in the epimer of the nonreducing terminal sugar moiety, but most such enzymes show a strong preference for one activity or the other. Rice Os3BGlu7 and Os7BGlu26 β-glycosidases show a less strong preference, but Os3BGlu7 and Os7BGlu26 prefer glucosides and mannosides, respectively. Previous studies of crystal structures with glucoimidazole (GIm) and mannoimidazole (MIm) complexes and metadynamic simulations suggested that Os7BGlu26 hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…To test the RDF value, it can show by the integration number on the first minimum value of heteroatoms in each inhibitor. 51 The 0EN–3CL pro complex showed that the N2 atom in the first peak at a distance of ∼0.3 nm had relatively high access to water molecules. In contrast, the rest of the heteroatoms in the 0EN–3CL pro complex (N1, N3, O1, O2, and O3) suggest low water molecule access to these atoms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test the RDF value, it can show by the integration number on the first minimum value of heteroatoms in each inhibitor. 51 The 0EN–3CL pro complex showed that the N2 atom in the first peak at a distance of ∼0.3 nm had relatively high access to water molecules. In contrast, the rest of the heteroatoms in the 0EN–3CL pro complex (N1, N3, O1, O2, and O3) suggest low water molecule access to these atoms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The calculation of absolute binding free energy was done by means of four highly efficient binding free energy methods: free energy perturbation (FEP), Bennett's acceptance ratio (BAR) method, thermodynamic integration (TI), and quadrature-based integration of TI. Good convergence of the predicted values ideally <1 kcal/mol among these statistical methods assessed the good agreement on the high complex stability [ 51 ]. The complete flow of steps followed in the current study is presented in Fig.…”
Section: Methodologiesmentioning
confidence: 99%
“…Despite this knowledge, important details of substrate stereo selectivity by β-glucosidases and β-mannosidases remain to be fully understood. Nutho and collaborators addressed this important problem and reported the structural data of the enzyme β-glucosidase Os3BGlu7 from rice (Oryza sativa), complemented with molecular modeling investigations of Os3BGlu7 β-glucosidase interaction with the epimeric inhibitors glucoimidazole (GIm) and mannoimidazole (MIm) [ 4 ].…”
Section: Structural Basis Of Specific Glucoimidazole and 2 Mannoimidazole Binding By The Enzyme β-Glucosidase Os3bglu7 From Ricementioning
confidence: 99%